Análisis de esfuerzos de compresión en el cráneo humano por medio del método del elemento finito - Nieto Miranda, J. Jesús; Minor Martínez, Arturo; Álvarez Gallegos, Jaime; Alonso Vanegas, Mario A.; Algorri Guzmán, María E. (Revista Mexicana de Ingenieria Biomedica, 2005)
We present the construction of a model of the human skull using the Finite Element Method. The geometry is given by 124 MRI images of the human head. The MRI images are digitized and the data are input into the Ansys Software (Ansys Inc) version 7.0. The model consists of 39,538 elements and 74,781 nodes. The physical properties that were considered were obtained from the scientific literature, the load and boundary conditions were applied in agreement with the position of a stereotactic frame fixed to the human head. In the analysis of intraskull stress, two positions were considered to apply four forces of compression to the skull. The intraskull pressure was also considered. The Von Mises stress patterns were calculated for each position, and the distribution of intraskull stress was obtained.